Fabrication and characterisation of FBG sensors in low loss polymer optical fibre - Lacraz, Amédéé; Theodosiou, Antreas; Polis, Michalis; Kalli, Kyriacos (My University, 2016)
In this paper, we report on an effective way to locally alter the refractive index of a low-loss polymer optical fibre (POF), in order to fabricate novel fibre optical sensors. Such refractive index modifications, if reproduced periodically, create fibre Bragg gratings (FBGs) that find diverse applications in telecommunications and sensing. With a femtosecond laser set-up, we were able to inscribe refractive index changes in the core of the fibre on an area as small as a μm2. This technique can be effectively used to produce FBGs with a tailored length and strength and, so, with desired optical properties. The fibre used was a large core, graded index, multimode perfluorinated fibre. FBGs resonate at different wavelengths depending on the mode distribution in multimode fibres, because the effective refractive index depends on the spatial distribution of the light inside the core. Therefore, the reflection spectrum from the grating degenerates into multiple resonances, each associated with a different mode. The detection of the reflected modes was performed with a custom made software that was able to track a specific reflected mode even when the FBG underwent perturbation, such as temperature or strain changes. Moreover, a key advantage of low-loss fibre is the possibility to use long lengths of fibre and to be able to inscribe several FBGs in a single piece of fibre. With our detection system, we managed to track the perturbation of individual FBGs in a fibre array of multiple gratings. The combination of our femtosecond inscription setup and a mode detection system is encouraging for the development of low loss POF sensing devices.
Keywords: Femtosecond laser; Fibre array; Fibre Bragg grating; Low loss fibre; Polymer optical fibre